Experimental study on the formation mechanism of landslides considering the spatial distribution of the locking section - Li, Xiaochao; Li, Dian; Kongde, Jingnan; Zhang, Zhihua; Li, Dongdong (Frontiers in Earth Science, 2026)
The evolution processes of locked-segment landslides are difficult to determine, causing severe economic losses and casualties. Furthermore, when the locked-segment landslide is excavated, its evolution process will become more complicated. However, there have been few studies on the identification criteria for the evolution state of locked-segment landslides. In this case, this paper adopted the model test to analyze the evolution process, deformation patterns, and stress distribution of locked-segment landslides, and the identification criteria for the evolution state were proposed. Specifically, for non-locked landslides, it presented general push-type progressive failure with multiple slip surfaces. The shape, depth, and deformation amount of the slip surfaces at each section of the slope were basically the same. As for the locked-segment landslide with a lower locking ratio (15%), the push-torsion progressive failure occurred, accompanied by multiple slip surfaces and non-cooperative deformation. The locked-segment landslide with a higher locking ratio (30%) presented as shallow push-type progressive failure. The shape, depth, and deformation amount of the slip surfaces at each section were also basically the same. The research results could provide significant reference for the identification, prevention, and early warning of locked-segment landslides.